Al-Islam and Kemuhammadiyahan Curriculum in Muhammadiyah Secondary School: An Analysis of Implementation and Development Material - Muhammad Ridlo; Hafidz (Ta'dib, 2024)
This study aims to analyze the implementation and development of the Al-Islam and Muhammadiyah (AIK) curriculum at SMP Muhammadiyah 7 Surakarta. This research approach uses a descriptive qualitative method with a focus on evaluating curriculum implementation and material development. Data collection was carried out through in-depth interviews, classroom observations, and analysis of curriculum documents. The results of the study show that although the implementation of the Al-Islam and Kemuhammadiyahan (AIK) curriculum at SMP Muhammadiyah 7 Surakarta has been going well, there are several challenges that need to be overcome, such as limited time in the implementation of classroom learning and the need to innovate teaching methods so that students are more interested. Not only that, the quality of teachers is a crucial fact in the implementation of the curriculum. This research provides insight into the importance of developing a curriculum that is adaptive to the changing times and student needs, as well as improving teacher competence in teaching Al-Islam and Muhammadiyah subjects.